Pengaruh Penggunaan Media Interaktif Go Domino terhadap Keterampilan Berhitung Siswa Kelas III SD - Syahriza Azzahrah; Kristiawati Kristiawati; Hamdana Hadaming (Universitas Muhammadiyah Magelang, 2026)
This study aims to determine the effect of the use of interactive media Go Domino on the numeracy skills of third-grade students of SD Inpres Bertingkat Mamajang 1. This study was motivated by the low numeracy skills of students caused by teacher-centered learning, lack of variety in learning methods, and minimal use of interesting and interactive learning media. This condition results in students being less active, less motivated, and having difficulty understanding basic mathematical concepts, especially addition and subtraction. This study used a quantitative approach with a pre-experimental design using a pretest-posttest model. The research sample consisted of 22 third-grade students. The research instruments used were observation sheets and numeracy ability test sheets to measure students' numeracy skills before and after treatment. Data analysis techniques used included descriptive statistics, normality tests, and hypothesis testing using paired sample t-tests. The results showed that the average pretest score was 46.13, which is included in the low category, then increased to 77.63 in the posttest, which is included in the high category. The results of the hypothesis testing showed a significance value of <0.001 <0.05, so Hâ‚€ was rejected and Hâ‚ was accepted. This indicates that there is a significant effect of the use of Go Domino interactive media on students' numeracy skills. Thus, the use of Go Domino interactive media has been proven to have a significant effect in improving students' numeracy skills.